Programa de formação continuada dos atendentes de emergência: uma proposta em construção - Siqueira, Thiago dos Reis (2017)
This dissertation is based on the importance and significance of the tasks carried out by the emergency police officers of the Military Police of São Paulo State Operations Center (COPOM / SP). The general purpose of the research is to analyze the curriculum proposal for the initial training of the emergency police officers, constructing paradigmatic codes for a continuous formation that considers the professional’s background and principles such as: integrity, dialogue, criticality, plurality and great respect for the dignity of the human person. This study aims to contribute to the improvement of the professional performance of the emergency attendants of COPOM / SP through the construction of knowledge and proposition of strategies that enable the reconception of training processes that allow effective behavioral changes. The theoretical foundations were systematized through a bibliographical research which main references are: Kant (2007), Adorno (2012), Apple (2006), Sacristán (1999), Freire (1996), Schön ), Weisz (2009), Garcia (1999), Feldmann (2009), Vasconcellos (2004), Silveira (2013). The research carried out is of a qualitative approach using documentary analysis. Among the main results of the analyzed data the critical understanding of the reality of the police emergency attendants of the COPOM / SP training stands out and, in extension, the perception of necessary requirements in relation to the continuous training, also covering the trainers. Regarding the training process, it is important to emphasize their collaborative sense of mutual respect, bearing in mind the meaning and social importance of emergency care, in order to preserve human dignity, its plurality and the sharing of experiences among professionals. The results of the analysis may be used as a reference for the redefinition of the procedures adopted by the Emergency Centers of the State of São Paulo or police stations that attend police incidents